The Civic Potential of Video Games - Kahne, Joseph (The John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning, 2009)
This report draws from the 2008 Pew Teens, Video Games, and Civics Survey, a national survey of youth and their experiences with video games done in partnership with Amanda Lenhart at the Pew Internet and American Life Project, with funding from the John D. and Catherine T. MacArthur Foundation. That survey led to the report, "Teens, Video Games, and Civics," which examines the nature of young people's video game play as well as the context and mechanics of their play. In addition to examining the relationship between gaming and youth civic engagement, "Teens, Video Games, and Civics" also provides a benchmark for video and online gaming among young people on a national level and the first broad, impartial look at the size and scope of young people's general gaming habits.